Nano graphene oxide hybridized polyacrylamide high-temperature-resistant fracturing fluid and preparation method thereof
Through the hybridization of nanographene oxide and polyacrylamide and the combination of metal composite crosslinking agent, a nanomodified thickener is formed, which solves the problems of degradation of rheological performance and large amount of thickener under high temperature conditions, and achieves higher temperature resistance and shear resistance and lower residue content.
Patent Information
- Application Number
- CN202311348119.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2025-04-18
AI Technical Summary
The existing high-temperature fracturing fluid system has deteriorated rheology performance under high temperature conditions, and the large amount of thickener is used to cause too much residue after the glue breaks, affecting oil and gas output.
Nanographene oxide is hybridized with polyacrylamide, combined with metal composite crosslinking agent and other additives to form a nanomodified thickener, which improves the temperature and shear resistance of the fracturing liquid.
It significantly improves the temperature and shear resistance of crosslinked frozen glue, reduces the amount of thickener, reduces the residue content after the glue is broken, and improves the oil and gas recovery rate.
Smart Images

Figure CN119842383A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil and gas field exploration and development, and specifically relates to a nano graphene oxide hybrid polyacrylamide high temperature resistant fracturing fluid and a preparation method thereof. Background Art
[0002] In recent years, with the increasing decline of shallow oil and gas resources, deep / ultra-deep oil and gas resources have become a hot area for exploration and development at home and abroad. Deep oil and gas resources are characterized by deep burial, high temperature and pressure, and low natural production capacity. They need to be hydraulically fractured to form a fracture network, increase the production capacity of a single well, and achieve economical and efficient exploitation.
[0003] Hydraulic fracturing technology is to pump a large amount of fluid from the ground into the target reservoir, rely on the hydraulic pressure to open the reservoir, form artificial cracks, and increase the flow channel of oil and gas. Fracturing fluid is a key factor affecting the effect of fracturing transformation, and the performance of fracturing fluid often determines the success or failure of fracturing construction. In view of the complex geological conditions of deep / ultra-deep layers, the existing fracturing fluid system is difficult to meet the needs of high-temperature deep well reservoir transformation, thus putting forward higher goals for fracturing fluid and more stringent performance requirements for fracturing fluid. For example, it is necessary not only to ensure that it still has good rheological properties under high temperature conditions to meet the needs of fracture formation and carrying proppant, but also to achieve multiple uses of one dose as much as possible, environmental protection without residue, and improve crude oil recovery.
[0004] The existing high temperature resistant fracturing fluid system is mainly considered from three aspects: thickener, crosslinker and temperature stabilizer used in fracturing fluid. Thickeners can be divided into guar gum and polymer according to type, and the crosslinkers used with them are organic boron, organic zirconium and boron zirconium composite crosslinkers, etc., and a small amount of temperature stabilizer is added on this basis to improve the high temperature resistance of the crosslinked fracturing fluid system. However, the existing high temperature resistant fracturing fluid system has the following problems:
[0005] ① The glycoside chains in the guar gum molecules break at 177°C. Even if it forms a cross-linked gel with an organic boron cross-linking agent, it is difficult to break the upper temperature limit of 180°C.
[0006] ② The core thickener of polymer fracturing fluid is polyacrylamide. However, the temperature and salt resistance of individual polyacrylamide polymers are poor. Most of them need to be copolymerized with acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, sulfonic acid monomers, etc. to form multi-polymers to improve the overall temperature and salt resistance. The production process of multi-polymers is complex, the yield is low, and the cost of use is relatively high. Most of the existing research is based on indoor experimental evaluation, which cannot be applied on a large scale;
[0007] ③ The amount of thickener used in the existing high temperature resistant fracturing fluid system is relatively large (0.4% to 0.6%), and it is difficult to achieve complete gel breaking, which means that there are still a lot of residues in the formation after gel breaking, which damages both the fractures and the reservoir, and is not conducive to the efficient production of oil and gas. Based on the many problems existing in the existing high temperature resistant fracturing fluid system, it is necessary to break the conventional technical thinking and develop a high temperature resistant fracturing fluid system with better performance from a new perspective.
[0008] The development of nanotechnology provides a new starting point for solving these problems. The nanomaterials added to the fracturing fluid thickener can interact with the flexible thickener molecular chain through hybrid modification. The nano-modified thickener formed by compounding has a stronger chain structure, thereby improving the temperature resistance and shear resistance of the fracturing fluid. Some scholars have begun to study the application of nanomaterials in improving the performance of fracturing fluids:
[0009] The invention patent with application publication number CN 201210143073.7 discloses a preparation method and application of clean fracturing fluid using nano-SiO2 association. The clean fracturing fluid system strengthened with nano-SiO2 can still maintain good rheological properties at 130°C. However, the cost of clean fracturing fluid is high, the use is limited, and the system cannot meet the transformation needs of high-temperature deep wells.
[0010] The invention patent with application publication number CN 201310132122.1 provides a method for preparing a polyacrylamide nanocomposite fracturing fluid thickener by in-situ polymerization of polyacrylamide and nano-inorganic phase. Although good temperature resistance is achieved under low concentration polyacrylamide conditions, the developed nano-inorganic phase is composed of an organic long-chain intercalation agent and a layered silicate mixed with magnesium nitrate and aluminum nitrate after an intercalation reaction. There are problems such as cumbersome and complicated processes, and the upper limit of the test temperature is only 150°C, which fails to break through a higher temperature limit.
[0011] The invention patent with application publication number CN 202110999967.5 provides a method for preparing clean, environmentally friendly, high-temperature resistant nano-fracturing fluid. The nanomaterial used is TiO2. By compounding modified lignin sulfonate, organic boron crosslinker, nano-material TiO2 and phase change filler, the long molecular chain of guar gum is hybridized to form a stable network structure, which can meet the requirements of heat resistance and shear resistance at 180°C. Although this method has improved the heat resistance of guar gum, there are many types of compound raw materials and complex production processes. In addition, the amount of guar gum used is still large, and the residue content after breaking the gel still needs to be considered.
[0012] Most of the existing nano-modified fracturing fluids are based on guar gum thickeners, and there are relatively few reports on nano-modified polyacrylamide polymers. In addition, most of the research is to improve the comprehensive performance of fracturing fluids by simply compounding nanomaterials and polymers. Summary of the invention
[0013] The technical problem to be solved by the present invention is to provide a nano-graphene oxide hybrid polyacrylamide high-temperature resistant fracturing fluid and a preparation method thereof in view of the deficiencies in the above-mentioned prior art, and to greatly improve the performance of the nano-modified system by adding a cross-linking agent, so as to solve the technical problem that the existing nano-materials cannot be used to greatly improve the comprehensive performance of the fracturing fluid.
[0014] The present invention adopts the following technical solutions:
[0015] A nano graphene oxide hybrid polyacrylamide high temperature resistant fracturing fluid, comprising:
[0016] 0.03wt.%-0.08wt.% of nano graphene oxide, 0.25wt.%-0.40wt.% of polyacrylamide polymer, 0.5wt.%-1.5wt.% of pH regulator, 0.20wt.%-0.35wt.% of metal composite cross-linking agent, 0.1wt.%-0.3wt.% of clay stabilizer, 0.03wt.%-0.10wt.% of degumming agent, 0.2wt.%-0.3wt.% of drainage aid, and the balance is water.
[0017] Specifically, the pH regulator is 1 mol / L hydrochloric acid solution; the metal composite cross-linking agent is organic zirconium or organic titanium; the clay stabilizer is a quaternary ammonium salt substance; the gel breaker is ammonium persulfate; and the drainage aid is a fluorocarbon surfactant, sodium dodecylbenzene sulfonate or nanoemulsion.
[0018] Furthermore, the organic zirconium cross-linking agent is a complex of zirconium oxychloride, glycerol and lactic acid.
[0019] Another technical solution of the present invention is a method for preparing a nano-graphene oxide hybrid polyacrylamide high temperature resistant fracturing fluid, comprising the following steps:
[0020] S1, adding natural graphite powder to a mixture of concentrated sulfuric acid, potassium persulfate and phosphorus pentoxide, stirring for reaction, adding pure water for suction filtration and washing to neutrality after cooling, to obtain pre-oxidized graphite powder;
[0021] S2, adding the pre-oxidized graphite powder obtained in step S1 into concentrated hydrochloric acid at 0-5°C, stirring at a constant temperature, and then adding sodium nitrate and potassium permanganate;
[0022] S3, stirring the product obtained in step S2 in a water bath until it becomes a paste, then adding pure water, stirring and dissipating heat, and adding hydrogen peroxide after constant temperature reaction;
[0023] S4, after diluting the system, filtering it with suction, washing it with dilute hydrochloric acid for multiple times to remove sulfate ions, and drying it under vacuum at low temperature to obtain a nano-graphene oxide product.
[0024] Specifically, in step S1, the stirring temperature is 70-90° C., and the reaction time is 5-7 h.
[0025] Specifically, in step S1, the mass ratio of concentrated sulfuric acid, potassium persulfate, phosphorus pentoxide and natural graphite powder is 35-45:2.5-3.5:1.8-2.2:9-11.
[0026] Specifically, in step S2, the mass ratio of concentrated hydrochloric acid, sodium nitrate, potassium permanganate and pre-oxidized graphite powder is: 35-45: 0.8-1.2: 3.6-4.4: 4.8-5.2, and the reaction time is 0.4-0.6h.
[0027] Specifically, in step S3, the stirring temperature of the water bath is 30-40° C., and the constant temperature reaction time is 1.5-2.5 h.
[0028] Specifically, in step S3, 10% to 15% of hydrogen peroxide having a concentration of 2.5% to 3.5% is added according to a mass ratio.
[0029] Specifically, in step S4, the number of times of washing with dilute hydrochloric acid is 3 to 5 times.
[0030] Compared with the prior art, the present invention has at least the following beneficial effects:
[0031] The nano graphene oxide hybrid polyacrylamide high temperature resistant fracturing fluid of the present invention is composed of a conventional fracturing fluid formula. After adding specially prepared nano graphene oxide and a composite metal cross-linking agent, the heat resistance and shear resistance of the formed cross-linked gel can be significantly improved.
[0032] Furthermore, 1 mol / L hydrochloric acid solution can alleviate the corrosion of the inner wall of the oil pipe by acid to the greatest extent, is easy to prepare and has a low construction risk factor; metal composite cross-linking agent organic zirconium or organic titanium is currently a common type of cross-linking agent for high temperature resistant cross-linked fracturing fluid system, and has the best cross-linking effect with polyacrylamide molecules. Quaternary ammonium salt clay stabilizers can effectively inhibit the expansion of clay minerals through various mechanisms such as surface adsorption, neutralization of charge, dispersion and hydration, and are currently the most widely used clay stabilizers in oil fields. Ammonium persulfate is an oxidative degumming agent, which has a fast degumming rate and low residue content for polyacrylamide-based polymer cross-linked fracturing fluid. Fluorocarbon surfactants, sodium dodecylbenzene sulfonate or nanoemulsions are used as drainage aids mainly because they can establish effective interfacial tension between water and oil, promote liquid drainage, improve dispersion and emulsification properties, reduce adhesion and foaming problems, and have high thermal stability.
[0033] Furthermore, firstly, zirconium oxychloride is a highly stable compound that can maintain its performance in high temperature environments, which is extremely important for the preparation of high temperature resistant cross-linked fracturing fluids; secondly, by adjusting the concentration and ratio of glycerol and lactic acid, the cross-linking properties of the organic zirconium cross-linking agent can be controlled. In addition, compared with some other cross-linking agents, organic zirconium cross-linking agents are generally more environmentally friendly because they do not introduce a large amount of toxic or harmful chemicals into the bottom of the well and groundwater.
[0034] A method for preparing a nanographene oxide hybrid polyacrylamide high temperature resistant fracturing fluid does not require advanced experimental conditions or special equipment and is suitable for large-scale preparation. At the same time, the method can introduce a large number of oxygen functional groups into the graphite structure, so that the graphene oxide has rich functional groups; due to the introduced functional groups, the graphene oxide has good dispersibility in water, which is convenient for preparing aqueous suspensions or solutions, and is easy to dissolve in polymer aqueous solutions, which is convenient for preparing fracturing fluids.
[0035] Furthermore, a high temperature of 70 to 90° C. helps to accelerate the reaction rate; a stirring time of 5 to 7 hours can fully oxidize the natural graphite powder.
[0036] Furthermore, sulfuric acid and potassium persulfate are strong oxidants that can oxidize the surface of graphite, introduce oxygen functional groups, and also separate the graphite layers. Phosphorus pentoxide acts as a catalyst in the reaction. These chemicals work together to destroy the layered structure of graphite, increase the gaps between graphite layers, and make subsequent oxidation reactions easier. Within the above mass ratio range, the pre-oxidation modification effect of natural graphite powder is the best, and the product agglomeration can be reduced.
[0037] Further, the presence of sodium nitrate and potassium permanganate is intended to further oxidize graphite. Although pre-oxidation has been carried out in the previous step, further oxidation can introduce more oxygen functional groups, increase the functional group content of graphene oxide (functional groups such as hydroxyl, carboxyl and ketone groups can increase the chemical activity and hydrophilicity of graphene oxide and improve its dispersibility in water), and destroy the graphite layer structure, making subsequent stripping and dispersion easier. In addition, sodium nitrate and potassium permanganate also help to remove residual impurities, making graphene oxide purer. The choice of mass ratio is because by controlling the amount of sodium nitrate and potassium permanganate added and the reaction time, the oxidation degree of graphene oxide can be accurately controlled; stirring in a 0°C constant temperature water bath helps to maintain the uniformity of the reaction, prevent the occurrence of local hot spots and uneven reactions, and ensure the uniformity of oxidation; and since potassium permanganate is a strong oxidant, controlling the reaction temperature at 0°C helps to reduce the danger in the reaction. This can improve the safety of the experiment.
[0038] Furthermore, the choice of temperature helps to stir the product of the previous oxidation step into a viscous state under relatively mild conditions. In the previous steps, strong acids and oxidants such as concentrated sulfuric acid, sodium nitrate and potassium permanganate were used for oxidation reactions. These chemicals may remain in the reaction, which may have an adverse effect on the properties of graphene oxide. Adding water to the product and stirring it helps to remove these residual substances, thereby purifying the graphene oxide; at the same time, it can neutralize the acidity of the liquid, and reducing the acidity helps to reduce the oxygen content of graphene oxide and control its properties. Adding water at the same time also helps to quickly dissipate heat and prevent the product from overheating.
[0039] Furthermore, the addition of hydrogen peroxide can effectively reduce and remove the residual oxidant in the above experimental steps and reduce the presence of impurities; the synthesized graphene oxide usually has abundant oxygen functional groups, but too many oxygen functional groups may reduce its conductivity and mechanical properties. Hydrogen peroxide can selectively reduce the content of oxygen functional groups, thereby adjusting the properties of graphene oxide. Nano-graphene oxide usually has poor dispersibility in water and is prone to agglomeration. After adding pure water and hydrogen peroxide, the dispersibility of graphene oxide can be improved, making it easier to disperse evenly in water, which is beneficial to the preparation of fracturing fluid.
[0040] Furthermore, the purpose of washing with dilute hydrochloric acid is to remove residual impurities and acidic substances to purify graphene oxide and ensure the stability of its quality and performance. The washing process helps to remove unreacted chemicals, fragments and impurities remaining in graphene oxide; at the same time, it can neutralize the residual acidity and adjust the pH value of graphene oxide to neutral or near neutral, which helps to maintain its stability. Through multiple washings, the purity of graphene oxide can be improved, possible residual impurities can be removed, and it can be more suitable for the preparation of subsequent fracturing fluids.
[0041] In summary, the preparation method of the present invention is simple, and the formed cross-linked gel can meet the requirements of temperature resistance and shear resistance at a low polymer addition amount, and is suitable for field application in high-temperature oil field fracturing.
[0042] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 A microstructure diagram of nano graphene oxide provided by the present invention;
[0044] Figure 2 A microscopic network structure diagram of the nano-graphene oxide hybrid modified polypropylene cross-linked fracturing fluid provided by the present invention;
[0045] Figure 3 A schematic diagram of the cross-linking mechanism of the nano-graphene oxide hybrid modified polypropylene cross-linked fracturing fluid provided by the present invention;
[0046] Figure 4 The rheological curve of the nano-graphene oxide hybrid modified polyacrylamide high temperature resistant fracturing fluid system obtained in Example 1 of the present invention at 150°C;
[0047] Figure 5 The rheological curve of the nano-graphene oxide hybrid modified polyacrylamide high temperature resistant fracturing fluid system obtained in Example 2 of the present invention at 160°C;
[0048] Figure 6 This is the rheological curve of the nano-graphene oxide hybrid modified polyacrylamide high temperature resistant fracturing fluid system obtained in Example 3 of the present invention at 180°C. DETAILED DESCRIPTION
[0049] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.
[0051] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0052] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.
[0053] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.
[0054] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6-22" means that all real numbers between "6-22" have been listed in this document, and "6-22" is just an abbreviation of these numerical combinations.
[0055] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.
[0056] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0057] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.
[0058] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.
[0059] The rheological properties of the fracturing fluid of polyacrylamide polymer alone are reduced due to the breakage of the molecular chain under high temperature and continuous shearing. Even if it forms a cross-linked gel structure with a cross-linking agent, the long molecular chain of polyacrylamide cannot be avoided from being destroyed. Therefore, the cross-linked system formed does not have excellent heat resistance and shear resistance. After the introduction of nano-graphene oxide, the hydrophilic groups on the surface of graphene will form covalent bonds with the hydroxyl groups on the polyacrylamide molecular chain, making the nano-graphene oxide a "node" in the composite structure, which can connect multiple polyacrylamide molecular chains.
[0060] Furthermore, after adding the cross-linking agent, the metal ions in the cross-linking agent form multi-point adsorption with graphene, which serves as synergistic cross-linking points, making the three-dimensional space of the entire cross-linking system more dense and complex, enhancing the stability and rigidity of the overall structure, and reducing the possibility of structural damage under continuous shear conditions. It can improve the temperature and shear resistance of the fracturing fluid to a certain extent, which is incomparable to the use of cross-linking agents and graphene alone.
[0061] The invention provides a nano graphene oxide hybrid polyacrylamide high temperature resistant fracturing fluid and a preparation method thereof. Nano graphene oxide is added to water in proportion, and in order to avoid agglomeration, the nano graphene oxide is placed in an ultrasonic disperser and dispersed for 15 minutes under the condition of an ultrasonic power of 19.86 Hz to ensure that the nano graphene oxide is uniformly dispersed in the aqueous solution; and then a clay stabilizer, a gel breaker, a drainage aid, polyacrylamide, a pH regulator and a cross-linking agent are added in sequence to prepare a cross-linked gel fracturing fluid.
[0062] The present invention discloses a nano graphene oxide hybrid polyacrylamide high temperature resistant fracturing fluid, comprising:
[0063] 0.03wt.%-0.08wt.% nano graphene oxide, polyacrylamide polymer 0.25wt.%-0.40wt.%, pH adjuster: 0.5wt.%-1.5wt.%, metal composite cross-linking agent: 0.20wt.%-0.35wt.%, clay stabilizer: 0.1wt.%-0.3wt.%, degumming agent: 0.03wt.%-0.10wt.%, drainage aid: 0.2wt.%-0.3wt.%, the balance is water.
[0064] Among them, the diameter of nano-graphene oxide is at the nanometer level, that is, less than 1 micron.
[0065] The molecular weight of polyacrylamide is 10 to 15 million.
[0066] The pH adjuster was 1 mol / L hydrochloric acid solution.
[0067] The metal composite cross-linking agent is organic zirconium or organic titanium.
[0068] Preferably, the organic zirconium cross-linking agent is a complex of zirconium oxychloride, glycerol and lactic acid.
[0069] Clay stabilizers are quaternary ammonium salts, such as epoxypropyltrimethylammonium chloride or 2-chloroethyltrimethylammonium chloride (CETA).
[0070] The gel breaker is ammonium persulfate.
[0071] The drainage aid is a fluorocarbon surfactant, sodium dodecylbenzene sulfonate or a nanoemulsion.
[0072] See also Figure 1 The nanographene oxide prepared by the above method presents a thin layer structure with obvious wrinkle characteristics, with certain undulations between the sheets, in a multi-layer stacked state, showing soft characteristics. In addition, it contains a small amount of lumps, which may be incompletely oxidized or unevenly dispersed graphite sheets or graphene oxide fragments.
[0073] See also Figure 2The microstructure of the hybrid modified polypropylene cross-linked fracturing fluid with nano-graphene oxide presents obvious spatial network structure characteristics. The size distribution of the mesh is between 12 and 55 nm, and the mesh shape is close to the hexagonal structure of graphene oxide. The mesh wall forms a thick skeleton structure with a skeleton diameter between 7 and 15 nm. The synergistic effect of nano-graphene oxide and the cross-linking agent makes the entire spatial network structure more compact, which is conducive to the enhancement of the rheological properties of the cross-linked fracturing fluid.
[0074] See also Figure 3 After the introduction of nano-graphene oxide into the polyacrylamide polymer solution, the hydrophilic groups on the graphene surface will form covalent bonds with the hydroxyl groups on the polyacrylamide molecular chain, making the nano-graphene oxide a "node" in the composite structure that can connect multiple polyacrylamide molecular chains. In addition, after the addition of the cross-linking agent, the metal ions in the cross-linking agent form multi-point adsorption with the graphene, which acts as a synergistic cross-linking point, making the three-dimensional space of the entire cross-linking system more dense and complex, enhancing the stability and rigidity of the overall structure, and reducing the possibility of structural damage under continuous shear conditions. It can improve the temperature resistance and shear resistance of the fracturing fluid to a certain extent.
[0075] The present invention discloses a method for preparing a nano graphene oxide hybrid polyacrylamide high temperature resistant fracturing fluid, comprising the following steps:
[0076] S1, graphite pre-oxidation treatment;
[0077] Add natural graphite powder to a mixture of concentrated sulfuric acid, potassium persulfate and phosphorus pentoxide, stir and react at 70-90°C for 5-7 hours, add pure water for suction filtration and wash until neutral after cooling.
[0078] In the pre-oxidation treatment stage, the mass ratio of concentrated sulfuric acid, potassium persulfate, phosphorus pentoxide and natural graphite powder is 35-45:2.5-3.5:1.8-2.2:9-11.
[0079] S2, low temperature reaction (0~5℃)
[0080] The pre-oxidized natural graphite powder is added into concentrated hydrochloric acid, placed in a 0°C constant temperature water bath and stirred, and then sodium nitrate and potassium permanganate are added.
[0081] In the low-temperature reaction stage, the mass ratio of concentrated hydrochloric acid, sodium nitrate, potassium permanganate and pre-oxidized graphite powder is: 35-45: 0.8-1.2: 3.6-4.4: 4.8-5.2; the reaction time is 0.4-0.6h.
[0082] S3, medium temperature reaction (35℃)
[0083] Place the product from the previous stage in a 30-40°C water bath and stir continuously until it becomes a paste. Then add pure water and stir to dissipate heat. After constant temperature reaction for 1.5-2.5 hours, add hydrogen peroxide.
[0084] S4, after diluting the system, filtering it with suction, washing it with dilute hydrochloric acid for multiple times to remove sulfate ions, and drying it under vacuum at low temperature to obtain a nano-graphene oxide product.
[0085] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0086] Example 1
[0087] Synthesis of Nano-graphene Oxide:
[0088] 10g natural graphite powder was added to a mixture of 21.74mL concentrated sulfuric acid, 3g potassium persulfate and 2g phosphorus pentoxide, stirred at 80℃ for 6h, and then filtered and washed to neutrality after cooling; 5g pre-oxidized product was weighed and added to 34.78mL concentrated hydrochloric acid, placed in a 0℃ constant temperature water bath and stirred, and then 1g sodium nitrate and 5g potassium permanganate solid were added to the beaker; the water bath temperature was raised to 35℃, and the mixture in the cup was continuously stirred with a glass cup until it became a paste, and then pure water was added to stir and dissipate heat, and 15mL of 3% hydrogen peroxide was added after standing at 35℃ for 2h; then 50mL of deionized water was added to dilute the product, and the dilution was filtered. The filtered product was washed 3 times with 1mol / L dilute hydrochloric acid solution, and finally the product was placed in a vacuum drying oven for drying, and nano graphene oxide was prepared.
[0089] Example 2
[0090] Synthesis of Nano-graphene Oxide:
[0091] 10g natural graphite powder was added to a mixture of 21.74mL concentrated sulfuric acid, 3g potassium persulfate and 2g phosphorus pentoxide, stirred at 90℃ for 5h, and then filtered and washed to neutrality after cooling; 5g pre-oxidized product was weighed and added to 34.78mL concentrated hydrochloric acid, placed in a 5℃ constant temperature water bath and stirred, and then 1g sodium nitrate and 5g potassium permanganate solid were added to the beaker; the water bath temperature was raised to 40℃, and the mixture in the cup was continuously stirred with a glass cup until it became a paste, and then pure water was added to stir and dissipate heat, and 20mL of 2.5% hydrogen peroxide was added after standing at 40℃ for 1.5h; then 50mL of deionized water was added to dilute the product, and the dilution was filtered. The filtered product was washed 5 times with 1mol / L dilute hydrochloric acid solution, and finally the product was placed in a vacuum drying oven for drying, and nano graphene oxide was prepared.
[0092] Example 3
[0093] Synthesis of Nano-graphene Oxide:
[0094] 10g natural graphite powder was added to a mixture of 21.74mL concentrated sulfuric acid, 3g potassium persulfate and 2g phosphorus pentoxide, stirred at 70℃ for 7h, cooled, filtered and washed to neutral; 5g pre-oxidized product was weighed and added to 34.78mL concentrated hydrochloric acid, placed in a 5℃ constant temperature water bath and stirred, then 1g sodium nitrate and 5g potassium permanganate solid were added to the beaker; the water bath temperature was raised to 30℃, and the mixture in the cup was continuously stirred with a glass cup until it became a paste, then pure water was added to stir and dissipate heat, and 12mL of 3.5% hydrogen peroxide was added after standing at 30℃ for 2.5h; then 50mL of deionized water was added to dilute the product, and the dilution was filtered. The filtered product was washed 4 times with 1mol / L dilute hydrochloric acid solution, and finally the product was placed in a vacuum drying oven for drying to prepare nano graphene oxide.
[0095] Example 4
[0096] Preparation of nano-graphene oxide hybrid modified polyacrylamide polymer fracturing fluid system:
[0097] 0.5g of graphene oxide was added to 979g of water. After ultrasonic dispersion, 2g of epoxypropyl trimethylammonium chloride, 0.5g of ammonium persulfate breaker, and 2.5g of fluorocarbon surfactant were added in sequence under stirring. After complete dissolution, 3g of polyacrylamide polymer (molecular weight of 12 million) and 10g of 1mol / L hydrochloric acid solution were added. After the polymer was fully swollen, 2.5g of organic zirconium crosslinking agent was added and stirred to form a nano-graphene oxide hybrid modified polyacrylamide polymer fracturing fluid. The prepared fracturing fluid system was sheared continuously at 150°C and a shear rate of 170s-1 for 2 hours, and the relationship curve between the apparent viscosity of the fracturing fluid and the change in time was measured, as shown in FIG. Figure 4 As shown in the figure, the increase in temperature will promote the cross-linking effect inside the fracturing fluid, which is manifested as an increase in viscosity. When the viscosity reaches the maximum value, it will gradually decrease as the shear proceeds, and the final average residual viscosity is 66.4 mPa·s.
[0098] Example 5
[0099] Preparation of nano-graphene oxide hybrid modified polyacrylamide polymer fracturing fluid system:
[0100] 0.6g of graphene oxide was added to 977.9g of water. After ultrasonic dispersion, 2g of epoxypropyl trimethylammonium chloride, 0.5g of ammonium persulfate breaker, and 2.5g of fluorocarbon surfactant were added in sequence under stirring. After complete dissolution, 3.5g of polyacrylamide polymer (molecular weight of 12 million) and 10g of 1mol / L hydrochloric acid solution were added. After the polymer was fully swollen, 3g of organic zirconium crosslinking agent was added and stirred to form a nano-graphene oxide hybrid modified polyacrylamide polymer fracturing fluid. The prepared fracturing fluid system was sheared continuously at 160°C and a shear rate of 170s-1 for 2 hours, and the relationship curve between the apparent viscosity of the fracturing fluid and the change in time was measured, as shown in FIG. Figure 5 As shown in the figure, the initial viscosity of the cross-linked fracturing fluid is high, but the viscosity decreases as the shearing progresses; the increase in temperature will promote the cross-linking effect inside the fracturing fluid, which is manifested as a continued increase in viscosity; when the viscosity reaches the maximum value, it will continue to decrease as the shearing progresses, and the final average residual viscosity is 113.8 mPa·s.
[0101] Example 6
[0102] Preparation of nano-graphene oxide hybrid modified polyacrylamide polymer fracturing fluid system:
[0103] 0.8g of graphene oxide was added to 976.7g of water. After ultrasonic dispersion, 2g of epoxypropyl trimethylammonium chloride, 0.5g of ammonium persulfate breaker, and 2.5g of fluorocarbon surfactant were added in sequence under stirring. After complete dissolution, 4.0g of polyacrylamide polymer (molecular weight of 12 million) and 10g of 1mol / L hydrochloric acid solution were added. After the polymer was fully swollen, 3.5g of organic zirconium crosslinking agent was added and stirred to form a nano-graphene oxide hybrid modified polyacrylamide polymer fracturing fluid. The prepared fracturing fluid system was sheared continuously at 180°C and a shear rate of 170s-1 for 2 hours, and the relationship curve between the apparent viscosity of the fracturing fluid and the change in time was measured, as shown in FIG. Figure 6 As shown in the figure, the initial viscosity of the cross-linked fracturing fluid is relatively high, and as the shearing progresses, the viscosity decreases continuously, with a slight increase in the middle, and the final average residual viscosity is 75.7 mPa·s.
[0104] Comparative Example
[0105] Comparative Examples 1-3 are, in comparison with Examples 4-6, no nano-graphene oxide is added, its mass is replaced by the mass of water, and the amounts of other additives remain unchanged.
[0106] Comparative Example 4 is, compared with Example 6, adding an equal amount of nano-graphene oxide, but not adding an organic zirconium cross-linking agent, and its mass is replaced by the mass of water, and the addition amount of other additives remains unchanged.
[0107] The results of the heat resistance and shear resistance rheological tests of the fracturing fluids of Examples 4-6 and Comparative Examples 1-4 are compared, as shown in Table 1.
[0108] Table 1
[0109]
[0110] It can be seen from the table that, under the premise that the addition amounts of other additives are completely consistent, the temperature resistance of the hybrid modified polyacrylamide polymer fracturing fluid is significantly improved after adding nano-graphene oxide.
[0111] Comparison of Example 3, Comparative Example 3 and Comparative Example 4 shows that, under the premise that the addition amounts of other additives are completely the same, the temperature resistance will also decrease when there is a lack of an organic zirconium cross-linking agent that has synergistic multi-point adsorption with graphene, indicating that there is a strong synergistic cross-linking effect between nano-graphene oxide and the organic zirconium cross-linking agent.
[0112] In summary, the present invention provides a method for preparing a nano-graphene oxide hybrid polyacrylamide high temperature resistant fracturing fluid. The nano-graphene oxide is prepared by a method that is highly operable, economical, safe and suitable for large-scale production; and the other additives of the fracturing fluid are all systems that are currently widely used in oil fields. The nano-hybrid polyacrylamide high temperature resistant fracturing fluid can achieve 180°C and 170s under the conditions of adding 0.03wt.%-0.08wt.% of nano-graphene oxide, 0.25wt.%-0.40wt.% of polyacrylamide polymer and 0.20wt.%-0.35wt.% of metal composite crosslinking agent. -1 With continuous shear resistance, the final residual viscosity can be maintained above 50mPa·s, meeting the performance requirements of high temperature resistant fracturing fluids at oil fields.
[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A nano graphene oxide hybrid polyacrylamide high temperature resistant fracturing fluid, characterized in that: include: 0.03wt.%-0.08wt.% of nano graphene oxide, 0.25wt.%-0.40wt.% of polyacrylamide polymer, 0.5wt.%-1.5wt.% of pH regulator, 0.20wt.%-0.35wt.% of metal composite cross-linking agent, 0.1wt.%-0.3wt.% of clay stabilizer, 0.03wt.%-0.10wt.% of degumming agent, 0.2wt.%-0.3wt.% of drainage aid, and the balance is water.
2. The nano graphene oxide hybrid polyacrylamide high temperature resistant fracturing fluid according to claim 1, characterized in that: The pH regulator is 1 mol / L hydrochloric acid solution; the metal composite cross-linking agent is organic zirconium or organic titanium; the clay stabilizer is a quaternary ammonium salt substance; the gel breaker is ammonium persulfate; and the drainage aid is a fluorocarbon surfactant, sodium dodecylbenzene sulfonate or nanoemulsion.
3. The nano graphene oxide hybrid polyacrylamide high temperature resistant fracturing fluid according to claim 2, characterized in that: The organic zirconium crosslinking agent is a complex of zirconium oxychloride, glycerol and lactic acid.
4. A method for preparing the nano-graphene oxide hybrid polyacrylamide high temperature resistant fracturing fluid according to claim 1, characterized in that: The following steps are involved: S1, adding natural graphite powder to a mixture of concentrated sulfuric acid, potassium persulfate and phosphorus pentoxide, stirring for reaction, adding pure water for suction filtration and washing to neutrality after cooling, to obtain pre-oxidized graphite powder; S2, adding the pre-oxidized graphite powder obtained in step S1 into concentrated hydrochloric acid at 0-5°C, stirring at a constant temperature, and then adding sodium nitrate and potassium permanganate; S3, stirring the product obtained in step S2 in a water bath until it becomes a paste, then adding pure water, stirring and dissipating heat, and adding hydrogen peroxide after constant temperature reaction; S4, after diluting the system, filtering it with suction, washing it with dilute hydrochloric acid for multiple times to remove sulfate ions, and drying it under vacuum at low temperature to obtain a nano-graphene oxide product.
5. The method for preparing nano graphene oxide hybrid polyacrylamide high temperature resistant fracturing fluid according to claim 4, characterized in that: In step S1, the stirring temperature is 70-90° C. and the reaction time is 5-7 h.
6. The method for preparing nano graphene oxide hybrid polyacrylamide high temperature resistant fracturing fluid according to claim 4, characterized in that: In step S1, the mass ratio of concentrated sulfuric acid, potassium persulfate, phosphorus pentoxide and natural graphite powder is 35-45:2.5-3.5:1.8-2.2:9-11.
7. The method for preparing nano graphene oxide hybrid polyacrylamide high temperature resistant fracturing fluid according to claim 4, characterized in that: In step S2, the mass ratio of concentrated hydrochloric acid, sodium nitrate, potassium permanganate and pre-oxidized graphite powder is: 35-45: 0.8-1.2: 3.6-4.4: 4.8-5.2, and the reaction time is 0.4-0.6h.
8. The method for preparing nano-graphene oxide hybrid polyacrylamide high temperature resistant fracturing fluid according to claim 4, characterized in that: In step S3, the stirring temperature of the water bath is 30-40° C., and the constant temperature reaction time is 1.5-2.5 h.
9. The method for preparing nano-graphene oxide hybrid polyacrylamide high temperature resistant fracturing fluid according to claim 4, characterized in that: In step S3, 10% to 15% of hydrogen peroxide having a concentration of 2.5% to 3.5% is added according to the mass ratio.
10. The method for preparing nano-graphene oxide hybrid polyacrylamide high temperature resistant fracturing fluid according to claim 4, characterized in that: In step S4, the washing with dilute hydrochloric acid is performed 3 to 5 times.
Citation Information
Patent Citations
Clean fracturing fluid system associated with nanomaterials and its application in oil and gas fields
CN103387827B
A method for preparing a polyacrylamide nanocomposite fracturing fluid
CN104109525B
Clean environment-friendly high-temperature-resistant nano fracturing fluid and preparation method thereof
CN113583652A
Cited By
Composite synergistic discharge aiding agent and preparation method thereof
CN120209813A
Low-temperature activated nano-composite cross-linking agent, fracturing fluid, and preparation method and application of low-temperature activated nano-composite cross-linking agent and fracturing fluid
CN121991679A